Iatrogenic bleeding of extracranial internal carotid artery aneurysm mimicking peritonsillar abscess - Sessa, Michele; Govoni, Marco; Piazza, Paolo; Di Lella, Filippo; Cuda, Domenico (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Extracranial Internal Carotid Artery Aneurysms are very rare. They can manifest with variable and unspecific clinical instances including neurologic symptoms associated with pulsatile cervical mass as the most frequent ones. This way, in presence of a mass in the oropharynx or neck, an aneurysm of the Internal Carotid Artery is not often considered as a prior diagnosis, therefore some of them are only discovered during surgical procedures. Here we describe a case of Extracranial Internal Carotid Artery Aneurysm misdiagnosed as a Peritonsillar Abscess which underwent surgical drainage. The purpose of this article is to emphasize factors which should be considered in differential diagnosis before doing inappropriate operative procedures. We will also focus on the effectiveness of Angiography, angio-CT and angio-MR in diagnosing the aneurysm and which factors to consider when choosing the best surgical or endovascular treatment.Method: Retrospective case report. Results: An Extracranial Internal Carotid Artery Aneurysm was misdiagnosed as a Peritonsillar Abscess which underwent surgical drainage with consequent profuse haemorrhage. An emergency tracheostomy was immediately performed. The patient was moved to the Interventional Neuroradiology Department where angiography revealed a double kinking and a giant aneurism of the Internal Carotid Artery. Endovascular permanent occlusion of the Internal carotid Artery was performed with detachable coils. The patient reported neither neurologic sequelae nor haemorrhage recurrence during the 2–year follow-up. Conclusions: Aneurysmatic dilation of Extracranial Internal Carotid Artery in the parapharyngeal space may determine, especially in presence of kinking, a medialization of the lateral oropharyngeal wall, mimicking a PTA. A high index of suspicion is mandatory for diagnosis.